IECON 2021 – 47th Annual Conference of the IEEE Industrial Electronics Society 2021
DOI: 10.1109/iecon48115.2021.9589158
|View full text |Cite
|
Sign up to set email alerts
|

Interface Compensation for More Accurate Power Transfer and Signal Synchronization within Power Hardware-in-the-Loop Simulation

Abstract: Power hardware-in-the-loop (PHIL) simulation leverages the real-time emulation of a large-scale complex power system, while also enabling the in-depth investigation of novel actual power components and their interactions with the emulated power grid. The dynamics and non-ideal characteristics (e.g., time delay, non-unity gain, and limited bandwidth) of the power interface result in stability and accuracy issues within the PHIL closed-loop simulations. In this paper, a compensation method is proposed to compens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Referring to ( 16) and (40a,b), it can be observed that the equations of the α and β components of the reconstructed currents in (42) incorporate dynamics of two different subsystems, one coming from the current reconstructed from the powers sent from Subsystem 2 and one from the phase angle of the voltage at Subsystem 1 PCC. The use of (34) to (36) to represent the dynamics of Subsystem 2, i.e. î′ d (s) in (40a,b), through those of Subsystem 1, i.e.…”
Section: B Asynchronous Coupling Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to ( 16) and (40a,b), it can be observed that the equations of the α and β components of the reconstructed currents in (42) incorporate dynamics of two different subsystems, one coming from the current reconstructed from the powers sent from Subsystem 2 and one from the phase angle of the voltage at Subsystem 1 PCC. The use of (34) to (36) to represent the dynamics of Subsystem 2, i.e. î′ d (s) in (40a,b), through those of Subsystem 1, i.e.…”
Section: B Asynchronous Coupling Modelmentioning
confidence: 99%
“…In addition, the transformation of the signals facilitates the incorporation of time delay compensation during the transformation of the signals back to time-domain quantities, an essential requirement for GDS due to the presence of larger inherent time delays. The transformations of signals has been more recently adopted for PHIL studies as well to realize more accurate setups incorporating time delay compensation [33], [34]. In [3], it was identified that the transformation of the interface signals impacts the stability of the GDS setup under consideration.…”
mentioning
confidence: 99%
“…Alternatively, as presented in [5], [24], the accuracy metrics including the power signal tracking error or the measurement to reference signal error, serve as an useful metrics to quantitatively assess the accuracy of the PHIL setups.…”
Section: ) Accuracymentioning
confidence: 99%
“…The impact of the non-ideal characteristics and the dynamics stemming from the PI on the PHIL system stability and accuracy has been extensively discussed in literature [20]- [24]. Many research efforts have been devoted to improve the stability and accuracy of the PHIL simulation, such as the impedance shifting method [4], multi-rate partitioning interface [19], Bergeron transmission line model based multitime-step interface [6], Smith-predictor based compensation [23], H ∞ optimal control based interface [5], the optimal compensation filter design [24], and other advanced methods as summarized in [25]. Detailed modelling principles, block diagrams, stability criteria, and accuracy metrics have been developed for the assessment of system properties such as stability and accuracy of respective approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation